Teenagers’ Anxiety in Facing the Transition of Adult Age in Song Lyrics of Blurryface Album by Twenty One Pilot (2015) - Ma'ruf Faunang (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2019)
The purpose of this research is to explain about how song lyrics in Blurryface album by Twenty One Pilot (2015) reflect the teenager’s anxiety How the teenager’s psychological condition in facing social pressure which in Twenty One Pilot’s song lyrics in Blurryface album (2015) The object and primary data used in this research are some song lyrics of Blurryface album as follows; Stressed Out, Ride, Lane Boy, Polarize, Heavy dirty soul and Doubt which whole the lyrics are written by Joseph Tyler. In conducting the process of the research, the researcher applied theory of psychoanalysis, focusing on teenager’s anxiety. The method applied in this research is qualitative method. The steps are reading, identifying, classifying, and selecting. In analyzing data, the researcher uses the steps such as displaying, explaining, and interpreting.